(untitled) (Delta Medical College Journal, 2017)
Obesity is a chronic metabolic disease characterized by an increase of body fat stores. It is a gateway to ill health, and has become one of the leading causes of disability and death, affecting not only adults but also children and adolescents worldwide. Obesity is a major risk factor for cancer, cardiovascular, metabolic, and respiratory disorders. This presents an ever increasing social and economic burden to individuals, families and the healthcare system. Preventing obesity is the optimal long-term population strategy. A comprehensive history, physical examination and laboratory assessment relevant to the patients obesity should be obtained. Appropriate goals of weight management emphasize realistic weight loss to achieve a reduction in health risks and should include promotion of weight loss, maintenance and prevention of weight regain. Management of co-morbidities and improving quality of life of obese patients are also included in treatment aims.Treatment should be based on good clinical care, and evidence-based interventions; should focus on realistic goals and lifelong multidisciplinary management. A comprehensive obesity management can only be accomplished by a multidisciplinary obesity management team. We conclude that physicians have a responsibility to recognize obesity as a disease and help obese patients with appropriate prevention and treatment. This review addresses the current therapeutic options in the treatment of obesity, focusing on pathogenesis, lifestyle changes, medications, and surgery. It also presents a suggested algorithm for the clinician assessing and managing obese patients. Delta Med Col J. Jan 2017 5(1): 35-48